Neospora caninum and reproductive wastage in extensively managed Queensland beef herds. Issue 9 (27th August 2013) - Fordyce, G; Holroyd, RG; Taylor, J; Kirkland, PD
<x xml:space="preserve">Abstract</x> Objective To compare reproduction in extensively managed, tropically adapted beef cows that were either seropositive or seronegative to Neospora caninum. Design Longitudinal study of cows within management groups. Methods Compare pregnancy with weaning outcomes for 502 seropositive and 3255 seronegative cows in 25 management groups. Results We found N. caninum in all herds, with an average of 20% of 2640 tested animals seropositive within management group; prevalence varied between 0% and 94%. At 7 of 10 sites assessed, there was evidence of horizontal transmission of N. caninum. There was no overall difference in pregnancy rate (79% vs 75%; P > 0.05), reproductive wastage after confirmed pregnancy diagnosis (11% vs 10%; P > 0.05) or weaning rate (67% vs 68%; P > 0.05) between seronegative and seropositive cows, respectively. In one herd where a combination of risk factors for N. caninum was present, a significant reduction in pregnancy rate occurred after the 6 months mating (85% vs 69%; P < 0.05). The fetal and calf losses observed were lowest in south‐east Queensland (4.3% of 117 pregnancies), highest in north‐west Queensland (15.5% of 413 pregnancies) and intermediate in north‐east Queensland (10.2% of 1625 pregnancies). Other infectious agents that are known to cause reproductive wastage were endemic in many herds, though none appeared to cause significant fetal or calf loss in this study. Conclusion Despite a high prevalence of N. caninum, there was no apparent effect on beef cattle reproduction, but there is potential to cause reproductive wastage if known risk factors to neosporosis are in effect.